VD-DVCC Based Current Mode SIMO Filter for Signal Processing Applications - Ramesh Mishra; Parimal Tiwari; Shambhavi Shukla (International Journal of Scientific Research in Science and Technology, 2025)
In this research a minimum component current mode (CM) single input multi output (SIMO) universal filter is proposed. The filter employs one voltage differencing differential voltage current conveyor (VD-DVCC), two grounded capacitors and a single grounded resistor. The filter can realize low pass (LP), high pass (HP), bandpass (BP), band reject (BR) and all pass (AP) responses simultaneously. The working of the filter is validated by designing it in 0.18µm technology in cadence design software at a supply voltage of ±0.9V.
Keywords: current mode; filter; signal processing; tunability